2018
DOI: 10.1590/0004-282x20180071
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of resistance training on the anxiety symptoms and quality of life in elderly people with Parkinson's disease: a randomized controlled trial

Abstract: The results of the present study indicate that resistance training is an effective intervention in the reduction of anxiety symptoms and improves the quality of life in elderly people with Parkinson's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
85
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(99 citation statements)
references
References 28 publications
0
85
0
5
Order By: Relevance
“…Treadmill and bicycle intervention can be used when performing against resistance [43][44][45]47]. Da Silva and her coworkers [48] suggest a long-term effect in nonmotor signs and symptoms of Parkinson's disease, especially in cognitive aspects, in individuals performing treadmill training, just as Ferreira and her coworkers [49] showed that resistance training was an effective intervention in the reduction of anxiety symptoms and improved the quality of life in this population.…”
Section: Resistance Training and Muscle Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Treadmill and bicycle intervention can be used when performing against resistance [43][44][45]47]. Da Silva and her coworkers [48] suggest a long-term effect in nonmotor signs and symptoms of Parkinson's disease, especially in cognitive aspects, in individuals performing treadmill training, just as Ferreira and her coworkers [49] showed that resistance training was an effective intervention in the reduction of anxiety symptoms and improved the quality of life in this population.…”
Section: Resistance Training and Muscle Strengthmentioning
confidence: 99%
“…In nonmotor signs and symptoms, aerobic training promotes positive and significant effects on global cognitive function, processing speed, sustained attention and mental flexibility, memory, and mood disorder aspects (anxiety and depression) in patients who are considered in a moderate stage of Parkinson's disease [49]. In sleep disorder, present in Parkinson's disease, aerobic exercise has been shown to have small-to-moderate effects.…”
Section: Aerobic Training: Treadmill Cycling Free Walking Dance Amentioning
confidence: 99%
“…Los ejercicios físicos y los deportes practicados de forma moderada tienen un potencial neuroprotector sobre la salud mental de la población en general, por el aumento del flujo sanguíneo y de la vascularización cerebral. Lo anterior favorece la estimulación de la producción de factores neurotróficos derivados del cerebro (BDNF, por sus siglas en inglés), que a su vez son responsables de la neurogénesis, angiogénesis, sinaptogénesis y neuroplasticidad (Ferreira et al, 2018).…”
Section: Introductionunclassified
“…To date, evidence-based treatment strategies for anxiety in PD are very limited 3 and studies focused on this subject are sorely needed. In this issue of Arquivos de Neuro-psiquiatria, Ferreira et al 7 report on the benefits of physical exercise -i.e., resistance training, in reducing anxiety symptoms and improving the perception of quality of life in PD. This is the first study to evaluate the effects of a resistance training program on anxiety in individuals with PD.…”
mentioning
confidence: 99%
“…Moreover, pharmacotherapy for anxiety and other nonmotor symptoms in PD may result in unfavorable adverse effects (especially in the case of benzodiazepines). The study by Ferreira et al 7 throws some light on this scenario, highlighting the role of exercise in the management of PD-related nonmotor symptoms.…”
mentioning
confidence: 99%